Association between dietary fat intake and colorectal cancer: A multicenter case-control study in Iran - Seyyedsalehi, Monireh Sadat; Collatuzzo, Giulia; Huybrechts, Inge; Hadji, Maryam; Rashidian, Hamideh; Safari-Faramani, Roya; Alizadeh-Navaei, Reza; Kamangar, Farin; Etemadi, Arash; Pukkala, Eero; Gunter, Marc J.; Chajes, Veronique; et al. (Frontiers in Nutrition, 2022)
The evolving trends in CRC as a one of the most common malignancies worldwide, have likely been influenced by the implementation of screening programs and changes in lifestyle habits. The changing lifestyle, including the shift in diet composition with higher fat, sugar, and animal-source foods intake, led to an increasing burden of CRC in countries undergoing rapid socioeconomic improvement. Results for the link between specific fatty acids (FAs) and CRC are generally inconclusive and more limited in developing countries than elsewhere.This study aims to look at the association between FA intakes and CRC and its anatomical subsites in a large Iranian case-control study. A food frequency questionnaire was used to collect information on dietary intake in 865 cases and 3206 controls. We conducted multivariate logistic regression models to calculate the odds ratio (OR) and 95% confidence interval (CI).We found positive association between CRC and high intake of dietary total fat (OR highest quartile Q4 =1.77, 95% CI=1.32-2.38), cholesterol (ORQ4 =1.58, 95% CI=1.22-2.05), and palmitoleic acid (ORQ4=2.16, 95% CI=1.19, 3.91), and an inverse association with high intake of dietary heptanoic acid (ORQ4=0.33, 95% CI=0.14, 0.79) and low intake of palmitic acid (OR lowest quartile Q2=0.53, 95% CI= 0.31-0.88). None of the fat variables were associated with rectal cancer. Our study suggests that the recommendation of limited consumption of fats may decrease the risk of CRC among the Iranian population.